Effect of inflation and liquidity on the Hedging of Oil Transactions by Participating in Gold Market: RS-DCC - Teymour Mohammadi; Sarah Akbari; Hamidreza Arbab; Reza Talebloo (اقتصاد باثبات, 2024)
Oil prices and other oil-products prices are connected and their price volatilities are parallel. Firms that are using crude oil in their products are facing the risk of price volatility which has different reactions in each era and is known under different oil regimes. When the economy faced volatility the market players faced loss and so to overcome this issue they began to hedge themselves with another commodity. This hedging process in different regimes has different rates. From the work of Hamiltonian (1989) oil price has its volatility and regimes so to this attitude there is an effort to find the effect of inflation and liquidity growth on efficient hedging ratios in different oil regimes. Monthly data of oil and gold prices for about 10 years from 2010 to 2020 is used and the model is programmed with MATLAB. The efficient hedge ratio for the first regime is 66 percent and the second one is 26 percent. In the periods when inflation and liquidity growth had an inappropriate trend, there was a lower grade for hedging oil prices with gold. There are two regimes for the price of oil which is for higher than 100 dollars and under 100 dollars and this historical situation happened in 2007 and 2009 either. In the period when the economy was experiencing high inflation and high liquidity growth, the optimal ratio of hedging decreased significantly, and in periods of low inflation, gold as a haven has been able to realize more optimal hedges..